2005
DOI: 10.1163/156853805774806223
|View full text |Cite
|
Sign up to set email alerts
|

Morphological integration of cranium and postcranial skeleton during ontogeny of facultative paedomorphic European newts (Triturus vulgaris and T. alpestris)

Abstract: The patterns of ontogenetic and interspecific variation of morphological integration (the relationships and correlation patterns of functionally and developmentally related morphological traits) in facultative paedomorphic species of two European newts (Triturus vulgaris and T. alpestris) were examined. The degree of morphological integration differed among ontogenetic stages. Variation in the level of morphological integration of cranium and postcranial skeleton during ontogeny of paedomorphic newts had the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…All analysed population samples, except for two, came from the G. DqukiT Herpetological Collection housed in the Institute for Biological Research "Sinina StankoviT," Belgrade. The sample from Bukumirsko Lake was previously used for the analysis of morphological integration and skull ontogeny (IvanoviT et al 2005(IvanoviT et al , 2007.…”
Section: Examined Materialsmentioning
confidence: 99%
“…All analysed population samples, except for two, came from the G. DqukiT Herpetological Collection housed in the Institute for Biological Research "Sinina StankoviT," Belgrade. The sample from Bukumirsko Lake was previously used for the analysis of morphological integration and skull ontogeny (IvanoviT et al 2005(IvanoviT et al , 2007.…”
Section: Examined Materialsmentioning
confidence: 99%
“…The large range of ecologies and developmental histories across lissamphibians, along with their impressive cranial diversity, suggest patterns of cranial integration in this clade may be complex. However, studies of European newts at the static level have found that the skull is highly integrated with no distinct modules (Ivanović et al, 2005;Ivanović & Kalezić, 2010), a result mirrored at the evolutionary level across the myobatrachid frog family (Vidal-García & Keogh 2017). Interestingly, static integration of the cranium is lower for paedomorphic forms of two European newts compared with fully metamorphosed forms, which can be explained by ontogenetic integration, where integration increases post-metamorphosis (Ivanović et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies of European newts at the static level have found that the skull is highly integrated with no distinct modules (Ivanović et al, 2005;Ivanović & Kalezić, 2010), a result mirrored at the evolutionary level across the myobatrachid frog family (Vidal-García & Keogh 2017). Interestingly, static integration of the cranium is lower for paedomorphic forms of two European newts compared with fully metamorphosed forms, which can be explained by ontogenetic integration, where integration increases post-metamorphosis (Ivanović et al, 2005). Mixed support was found for a range of three to five module models across different toad species of the Rhinella granulosa complex (Simon & Marroig, 2017), and for caecilians, a two-module model was found as best supported for the skull at both the evolutionary and static level (Sherratt, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we prefer the former scenario from a pure parsimony standpoint, the latter cannot be ruled out with this dataset. Additionally, a number of studies have documented fluctuations in integration over ontogeny (Cheverud et al 1983;Cheverud and Leamy 1985;Zelditch 1988;Zelditch and Carmichael 1989;Cane 1993;Ackermann 2005;Ivanovic et al 2005), so this question remains open. For example, if these epigenetic factors do not have an effect on integration, then other interactions that do not vary in these groups may have driven the convergence in integrative pattern.…”
Section: Discussionmentioning
confidence: 99%